2020
DOI: 10.1038/s41419-020-03268-1
|View full text |Cite|
|
Sign up to set email alerts
|

RNA-binding protein SORBS2 suppresses clear cell renal cell carcinoma metastasis by enhancing MTUS1 mRNA stability

Abstract: RNA-binding proteins (RBPs) predominantly contribute to abnormal posttranscriptional gene modulation and disease progression in cancer. Sorbin and SH3 domain-containing 2 (SORBS2), an RBP, has been reported to be a potent tumor suppressor in several cancer types. Through integrative analysis of clinical specimens, we disclosed that the expression level of SORBS2 was saliently decreased in metastatic tissues and positively correlated with overall survival. We observed that overexpression of SORBS2 brought about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…RBM14 encodes a ribonucleoprotein that functions as a general nuclear coactivator and an RNA splicing modulator in a PARP-dependent DSB repair process [ 29 ]. MTUS1 , a tumour-suppressor gene encoding angiotensin-II type 2 receptor-interacting proteins, is downregulated in clear cell renal cell carcinoma [ 31 ]. However, whether these mutations alter the clinical treatment of CDC patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…RBM14 encodes a ribonucleoprotein that functions as a general nuclear coactivator and an RNA splicing modulator in a PARP-dependent DSB repair process [ 29 ]. MTUS1 , a tumour-suppressor gene encoding angiotensin-II type 2 receptor-interacting proteins, is downregulated in clear cell renal cell carcinoma [ 31 ]. However, whether these mutations alter the clinical treatment of CDC patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, RNA binding proteins (RBPs) have attracted growing attention in multiple diseases (31), particularly in tumors such as triple-negative breast cancer (32), clear cell renal cell carcinoma (33), and pancreatic cancer (34). RBPs also play a role in HCC (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, p53-regulation of ATIP1 transcripts suggested a link between MTUS1 gene regulation and cancer [ 18 ]. Indeed, MTUS1 down-regulation in cancer tissues was frequently reported, including in tumors from the breast [ 19 , 20 , 21 , 22 , 23 ], bladder [ 24 , 25 ], colon [ 26 , 27 , 28 , 29 ], gallbladder [ 30 ], gastric tissues [ 31 , 32 ], lung (NSCLC) [ 33 ], head-and-neck [ 34 , 35 , 36 , 37 , 38 , 39 ], clear cell renal cell carcinoma (cc-RCC) [ 40 , 41 ], and uveal melanoma [ 42 ], with the exception of prostate cancer, in which MTUS1 expression was reported to increase with cancer progression [ 43 , 44 ] ( Table 1 ). Only few studies were designed to discriminate between different ATIP isoforms, and they all pointed to ATIP3 as the major MTUS1 isoform altered in human malignancies [ 19 , 21 , 36 , 43 ], ATIP1 being a minor form expressed in normal peripheral tissues [ 14 ].…”
Section: Atip3 and The Mtus1 Gene A Historical Point Of Viewmentioning
confidence: 99%
“…In an independent study conducted in renal cancer cells, ATIP3 was found to regulate the phosphorylation of KIF2C (also designated MCAK), another microtubule depolymerizing kinesin of the KinI family. A recombinant fragment of ATIP3 was shown to contribute to KIF2C phosphorylation on serine 192 by Aurora kinase B, and increase tubulin polymerization, consistent with its microtubule stabilizing effects [ 40 ].…”
Section: Cancer-related Molecular Mechanisms Controlled By Atip3mentioning
confidence: 99%
See 1 more Smart Citation